Evaluasi Pengelolaan Sampah Kecamatan Gresik Kabupaten Gresik Ditinjau Dari Aspek Teknis - Mohammad Fardi Habibi; Wahyono Hadi; Achmad Chusnun Ni'am (Al-Ard: Jurnal Teknik Lingkungan, 2023)
Solid waste management is a serious challenge for the government in making policies, so integrated and sustainable waste management is needed. Gresik Regency is one of the areas that support the development of the city of Surabaya so it is experiencing rapid growth in all sectors. The condition of the capacity of the Ngipik landfill waste cell serving the Gresik sub-district has experienced an overload. The problem in this research is how solid waste management in Gresik district is viewed from the technical aspect with an evaluation that refers to the applicable laws and regulations on waste so that the research objectives are obtained by analyzing the technical aspects. This study uses quantitative data and qualitative data methods and then analyzed them by conducting a review of aspects related to the validity of existing conditions according to normative standards and waste management theory. The evaluation results obtained as follows: The level of waste reduction has not yet reached 30% and waste services in Gresik sub-district by: 100%, there is still at least a willingness to store segregated containers, there are still TPS without roofs, transportation has been fulfilled but the fleet and containers are still available, not feasible, the location of the Ngipik landfill is feasible based on SNI 03-3141-1994.